Flexural strength, fracture toughness, three-body wear, and Martens parameters of pressable lithium-X-silicate ceramics. Issue 3 (March 2020) - Stawarczyk, Bogna; Dinse, Lina; Eichberger, Marlis; Jungbauer, Rebecca; Liebermann, Anja
Abstract: Objectives: To test and compare five pressable lithium-X-silicate-ceramics on their mechanical and wear properties. Methods: Specimens were pressed and prepared from: i. Amber Press (AP), ii. Celtra Press (CP), iii. Initial LiSi Press (IL), iv. Livento Press (LP), and v. IPS e.max Press (IE). Four-point flexural strength (FS), SEVNB fracture toughness (KIC ), three-body wear (3BW), Martens hardness (HM) and indentation modulus (EIT ) were measured. For CP, FS and HM were measured with and without additional Power Firing. Each subgroup contained 15 specimens. Data were analyzed using Kolmogorov–Smirnov, one-way ANOVA followed by Scheffé test, Kruskal–Wallis-H-, Mann–Whitney-U-, and Spearman–Rho-test (p < 0.05). The Weibull modulus was calculated using the maximum likelihood estimation method. Results: AP and CP presented higher FS than IL. LP presented the highest Weibull modulus. CP showed lower KIC values than AP, and AP was not significant compared to LP and IE. The most 3BW material loss was observed for CP. CP revealed higher HM values than the remaining ceramics. IL presented lower EIT compared to AP and CP. The following correlations were observed between the test parameters: 3BW with FS (r = 0.279, p = 0.015), with HM (r = −0.378, p = 0.001), and with EIT (r = −0.344, p = 0.004); EIT with FS (r = 0.203, p = 0.028); and HM with FT (r = −0.223, p = 0.027) and EIT (r = 0.884, p < 0.001). No correlations were observed between FS and KIC (r = 0.046; p = 0.346). Significance: AP followed by LP showed the highest and IL followed by CP the lowest properties tested. Power Firing of CP improved the flexural strength. Ceramics with high flexural strength and Martens parameters showed lower wear. Materials with high Martens hardness presented lower fracture toughness values and ones with high indentation modulus showed high flexural strength.